Habitat compression exacerbates human-macaque conflicts: Implications for regional management in karst southwest China - Zhicheng Zhang; Manfang He; Ye Li; Haijun Su (Nature Conservation)
The escalating incidence of human-wildlife conflicts involving protected species has posed a significant challenge in global conservation. Although population growth, a byproduct of successful conservation, has often been pinpointed as a key factor, the impact of human-induced land use changes and habitat loss on conflict occurrence has not been well comprehended, especially at broader regional levels. In China’s mountainous southwest, conflicts between humans and the nationally protected rhesus macaque (Macaca mulatta) have intensified due to agricultural encroachment into forested zones. This study integrates species distribution data (309 occurrence points) and conflict incident records (252 sites) across a 16,800 km2 karst landscape to evaluate habitat suitability under natural versus anthropogenic scenarios using the MaxEnt model. Our findings reveal that Precipitation of Wettest Quarter (bio16), Normalized Difference Vegetation Index (NDVI), Mean Diurnal Temperature Range (bio2), Minimum Temperature of the Coldest Month (bio6), and Human Population Density (pop) are the predominant determinants of macaque habitat suitability at a regional scale. There is a substantial spatial correlation between high habitat suitability zones and areas prone to conflict incidents. Moreover, human activities have markedly modified the extent and distribution of macaque habitats. Our results imply that the escalating severity of protected species incidents at a regional scale may not be solely due to population growth but also to human-driven land use changes that increase the spatial overlap between suitable habitats and human activity areas. Consequently, effective management strategies for protected species incidents should place a heightened emphasis on habitat modifications.